Efficient circular gene knockout system for Burkholderiales strain DSM 7029 and Mycobacterium smegmatis mc2 155. (12th June 2019) - Lei, Xiaolai; Fan, Qiuxia; Huang, Tian; Liu, Haiyun; Zhao, Guoping; Ding, Xiaoming
Abstract: Multiple gene knockouts are often employed in studies of microbial physiology and genetics. However, the selective markers that confer antibiotic resistance are generally limited, so it is necessary to remove these resistance genes before the next round of using, which is time consuming and labor intensive. Here, we created a universal circular gene knockout system for both the gram-negative bacterial Burkholderiales strain DSM 7029 and the gram-positive bacterial Mycobacterium smegmatis mc 2 155, by combining the homologous recombination with multiple serine integrase-meditated site-specific recombination systems. In this system, a resistance gene and an integrase gene were constructed within the two attachment sites corresponding to a second, different integrase to form a cassette for gene disruption, which could be easily removed by the second integrase during the subsequent round of gene knockout. The sacB gene was also employed for negative selection. As the integrase-mediated deletion of the resistance/integrase gene cassette was highly efficient and concurrent with the following knockout round, the cyclic use of three cassettes could achieve multiple gene knockout in a sequential manner. Following the modularity concept in synthetic biology, common components of the knockout plasmids were retained as BioBricks, accelerating the knockout plasmids construction process. The circular gene knockout system can also be used for multiple gene insertions and applied to other microorganisms.